The Effect of Mini Zoo Educational Game Tools on Natural Intelligence in Early Childhood Aged 5-6 Years - Kamilah, Nurul; Heldanita, Heldanita; Suryanti, Dewi Sri; Susanti Harahap, Fatimah Depi; Irawan, Yossy; Rohayani, Farida; bt Samaun, Siti Salina (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the effect of using the Mini Zoo educational game tool on the natural intelligence of children aged 5-6 years. The research employed a quantitative approach with an experimental design involving a single group. The sample consisted of 20 children from Group B3 at RA Az Zahra. The results indicate that the null hypothesis (HÔéÇ) was rejected, while the alternative hypothesis (HÔéÉ) was accepted, demonstrating a significant effect of the Mini Zoo educational game tool on children's natural intelligence. The findings imply that exploration-based educational tools such as Mini Zoo are effective for improving young children's natural intelligence. Therefore, incorporating similar educational game tools is recommended for early childhood learning activities.